Pelestarian Nilai-Nilai Kearifan Budaya Lokal dalam Menjaga Harmonisasi Manusia dan Lingkungan Alam di Desa Ngalukoja Kabupaten Ende - Zainur Wula; Puspas Setyaningrum (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2026)
This study aims to examine the preservation of local cultural wisdom values ​​in maintaining harmony between humans and the natural environment in Ngalukoja Village, Ende Regency. The study used a qualitative approach with data collection techniques through in-depth interviews and participant observation, and analyzed descriptively. The results of the study indicate that local cultural wisdom has been preserved for hundreds of years by mosalaki (traditional leaders) together with the faiwalu anakalo community. Two main rituals in the agricultural cycle are carried out annually, namely the ngua ritual in November to mark the start of the planting season, and the keti uta ritual in April to mark the harvest period. Before these two rituals, an offering ceremony is held to the spirits of the ancestors in the form of rice and meat placed on a koja kanga (a sacrificial stone that also functions as an ancestral grave), led by the mosalaki through prayers and mantras to ask for safety, blessings, and good agricultural results. In addition to rituals, preservation also includes the preservation of heirlooms and traditional arts such as gongs, drums, and traditional dances. It was concluded that all these practices contain religious-magical values ​​that serve as symbols of cultural identity and as a means of maintaining a balanced relationship between humans and nature and their ancestors.